INDUSTRIAL ACCIDENTS SURVEY: METHODOLOGICAL PROPOSITION ETUDE DES ACCIDENTS INDUSTRIELS: PROPOSITION METHODOLOGIQUE - ABIBSI, A.; DJEBABRA, M.; BAHMED, L. (Courrier du Savoir, 2014)
The survey of work accidents requires a very important information flux which is possible to structure only through a methodological proceedure. This study confirms this proposal and suggests a way of survey of industrial accidents that permits the organization of information related to work accidents and the specific methods allowing the survey of this type of industrial incidences. Keywords: technological and human factors methods of survey, causes tree.